Endométriose et travail, un calvaire au féminin - Poissonnier, Gaétane (Alternatives Economiques, 2021)
Number: 2 Publisher: Alternatives économiques
Keywords: 1900-1999; 1960-1969; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; corps; cours; discipline; endométriose; europe; france; inégalités; justice reproductive; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail

The feminist political economy of Covid-19: Capitalism, women, and work. - Cohen, Jennifer; van der Meulen Rodgers, Yana (Global public health, 2021)
Analysing the pandemic through a feminist political economy lens makes clear how gender, race, and class structures are crucial to the functioning of capitalism and to understanding the impacts of the pandemic. The way capital organises production and reproduction combines with structures of oppression, generating vulnerability among the racialised and gendered populations worst impacted by Covid-19. Using global data, this commentary shows that during the pandemic, women experienced relatively greater employment losses, were more likely to work in essential jobs, and experienced a greater reduction in income. Women were also doing more reproductive labour than men and were more likely to drop out of the labour force because of it. Analyses of capitalism in feminist political economy illustrate how capital accumulation depends on women's oppression in multiple, fundamental ways having to do with their paid and unpaid work. Women's work, and by extension their health, is the foundation upon which both production and social reproduction rely. Recognising the pandemic as endogenous to capitalism heightens the contradiction between a world shaped by the profit motive and the domestic and global requirements of public health.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; capitalisme; covid-19; histoire et politique; patriarcat; projet charge mentale; périodes historiques; racisme; ressource en ligne; santé; sexisme; systèmes d'oppressions; thématiques; violences

Associations between perceived discrimination and contraceptive method use: why we need better measures of discrimination in reproductive healthcare - Loder, Charisse; Hall, K.; Kusunoki, Yasamin; Harris, Lisa Hope; Dalton, Vanessa (Women & Health, 2021)
Discrimination has historically contributed to coercive contraceptive in the United States. We investigated associations between perceived discrimination, or the perception of unequal treatment in everyday life, and contraceptive method use among U.S. women. We analyzed population-based data from a 2013 study of U.S. women who were premenopausal, age 18–50, sexually active with a male partner in the last year and were not attempting pregnancy. Perceived discrimination was measured using the Everyday Discrimination Scale. Contraceptive method use was categorized into five method categories: permanent, highly effective reversible, moderately effective, barrier and no method. We analyzed relationships between perceived discrimination and contraceptive method use with several regression models, controlling for covariates. Among 539 women in our analytic sample, those with high perceived discrimination had lower incomes, less educational attainment and were less likely to be insured. Perceived discrimination was associated with a reduced odds of using any contraceptive method (aOR 0.43, CI 0.21–0.87, p < .001). Contraceptive method users with high perceived discrimination had an increased odds of using highly effective reversible methods versus moderately effective methods (aOR 5.28, CI 1.63–17.07 p = < .001). Women who perceived discrimination were at risk for contraceptive nonuse; however, among contraceptive users, perceived discrimination was associated with the use of more effective reversible methods.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; contraception; cours; discipline; discriminations; intersectionnalité; inégalités; justice reproductive; médecine; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; santé; sciences; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

Systems thinking in COVID-19 recovery is urgently needed to deliver sustainable development for women and girls - Omukuti, Jessica; Barlow, Matt; Giraudo, Maria Eugenia; Lines, Tallulah; Grugel, Jean (The Lancet Planetary Health, 2021)
In low-income and middle-income countries, such as those in sub-Saharan Africa and Latin America, the COVID-19 pandemic has had substantial implications for women’s wellbeing. Policy responses to the COVID-19 pandemic have highlighted the gendered aspect of pandemics; however, addressing the gendered implications of the COVID-19 pandemic comprehensively and effectively requires a planetary health perspective that embraces systems thinking to inequalities. This Viewpoint is based on collective reflections from research done by the authors on COVID-19 responses by international and regional organisations, and national governments, in Latin America and sub-Saharan Africa between June, 2020, and June, 2021. A range of international and regional actors have made important policy recommendations to address the gendered implications of the COVID-19 pandemic on women’s health and wellbeing since the start of the pandemic. However, national-level policy responses to the COVID-19 pandemic have been partial and inconsistent with regards to gender in both sub-Saharan Africa and Latin America, largely failing to recognise the multiple drivers of gendered health inequalities. This Viewpoint proposes that addressing the effects of the COVID-19 pandemic on women in low-income and middle-income countries should adopt a systems thinking approach and be informed by the question of who is affected as opposed to who is infected. In adopting the systems thinking approach, responses will be more able to recognise and address the direct gendered effects of the pandemic and those that emerge indirectly through a combination of long-standing structural inequalities and gendered responses to the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afrique; afrique subsaharienne; amérique latine; amériques; approches et analyses; environnement; justice climatique; justice sociale; pandémie; patriarcat; politiques publiques; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé publique; sexisme; systèmes d'oppressions; thématiques

Undocumented mothers and work–family conflict in restrictive policy contexts - Straut-Eppsteiner, Holly (Journal of Marriage and Family, 2021)
Objectif Cette recherche examine la manière dont les mères latines sans papiers négocient le conflit travail-famille dans un contexte de politiques d’immigration restrictives. Arrière-plan Aux États-Unis, les femmes continuent de lutter contre les tensions entre travail et famille, et les femmes pauvres sont confrontées à des contraintes particulières. Les immigrées latinos se sont de plus en plus installées et ont fondé des familles aux États-Unis, et ont rejoint le marché du travail dans des emplois à bas salaires. Contrairement aux femmes nées aux États-Unis, ces femmes doivent faire face à des politiques d’immigration restrictives, ce qui suggère de nouveaux domaines de compréhension des inégalités intersectionnelles qui façonnent le conflit travail-famille. Méthode Les résultats sont basés sur des entretiens approfondis menés auprès de 45 mères immigrantes latinos en Caroline du Nord qui avaient une expérience du marché du travail rémunéré. Les sujets d'entretien comprenaient la famille, le travail et la migration tout au long de la vie des femmes. Résultats Les contextes politiques spécifiques au lieu, les conditions de travail, les attentes patriarcales et le manque d'accès aux réseaux de soins remettent en question la capacité des immigrantes latines à remplir le double rôle de mère qu'elles occupent à la fois en tant que pourvoyeuses de famille et en tant que soignantes et nourricières de leurs enfants. Conclusion Les attentes sociales liées à la maternité ajoutent une dimension de précarité au statut vulnérable des femmes en tant que travailleuses sans papiers et démontrent l’impact genré des politiques d’immigration. Conséquences Les politiques restrictives rendent de plus en plus difficile pour les femmes sans papiers d’obtenir ou de changer d’emploi sur le marché du travail à bas salaires. Les résultats soulignent l’importance de prendre en compte le statut d’immigrant dans les études sur les conflits travail-famille, en particulier à l’heure où les politiques ciblant les immigrés s’intensifient.
Keywords: amériques; approches et analyses; conciliation famille-travail; famille; femmes latino-américaines; femmes migrantes*; inégalités; patriarcat; politiques migratoires; projet charge mentale; racisme; régions géographiques; santé; santé mentale; sexisme; systèmes d'oppressions; thématiques; travail; travail reproductif; états-unis

Guérison Collective Healing - Yuen, Felice; Gabriel, Wanda; Fast, Elizabeth (Guérison Collective Healing, 2021)
Aborder les expériences des femmes autochtones dans les prisons provinciales du Québec Vers une guérison collective Addressing the experiences of Indigenous women in Quebec’s provincial prison Towards Collective Healing
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; canada; communauté; cours; discipline; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; militance; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système carcéral; système colonial; systèmes d'oppressions; thématiques; travail social; violences